Pendampingan Bimbingan Belajar Baca Tulis untuk Mengatasi Kesulitan Literasi pada Siswa Kelas Atas Desa Karang Anyar - Sugiarti; Fitriyah, Lailatul; Sugiarti, Riska (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
This reading and writing tutoring assistance program was implemented as an effort to overcome literacy difficulties experienced by upper-grade elementary students in Karang Anyar Village. Literacy problems, particularly in reading and writing skills, have become a serious concern as they directly affect students' academic performance and critical thinking abilities. The program was carried out using a participatory approach with tutoring methods tailored to the needs and skill levels of the students. The assistance was conducted regularly with materials focusing on improving reading comprehension and writing simple narratives. The results of the program showed an improvement in students' literacy skills, including reading fluency, comprehension of reading materials, and the ability to express ideas in written form. This program demonstrates that well-directed and continuous assistance can be an effective solution to address literacy challenges at the elementary school level, especially in rural areas such as Karang Anyar Village.